2018
DOI: 10.1159/000484559
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Population Viability of Three Independent Javan Gibbon (Hylobates moloch) Populations on Java, Indonesia

Abstract: Population viability analysis is a predictive procedure that uses a combination of different modelling approaches to estimate species vulnerability to extinction. Javan gibbons (Hylobates moloch) are vulnerable to local extinction primarily due to loss of habitat and hunting for the illegal pet trade. Using the modelling software VORTEX, we assessed the status of Javan gibbons in 3 areas (Ujung Kulon National Park, Halimun-Salak National Park, and Dieng Mountains) which hold over half of the remaining estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…These and other as yet unknown impacts are expected to continue and worsen unless the underlying causes can be tackled, adding an additional major threat to biodiversity and increasing extinction risk for many species. Understanding the complex use of space of these territorial animals is important in assessing both carrying capacity [43,89], how dispersing gibbons use space and establish a territory [9,9092] and understading how reintroduced gibbon pairs will establish their core and HR [93–97].…”
Section: Discussionmentioning
confidence: 99%
“…These and other as yet unknown impacts are expected to continue and worsen unless the underlying causes can be tackled, adding an additional major threat to biodiversity and increasing extinction risk for many species. Understanding the complex use of space of these territorial animals is important in assessing both carrying capacity [43,89], how dispersing gibbons use space and establish a territory [9,9092] and understading how reintroduced gibbon pairs will establish their core and HR [93–97].…”
Section: Discussionmentioning
confidence: 99%
“…In a population viability analysis, Jaima Smith and colleagues calculated the extinction probability over a 100-year time period under various scenarios involving variable degrees of deforestation and loss of gibbons due to illegal hunting/ trade. Smith et al (2017) determined that the gibbon population at UKNP is indeed viable, provided their estimates for annual hunting losses can be avoided at all costs. Unfortunately, as I have recorded at Sancang, relatively widespread reverence for the forest and its denizens does not produce an infallible immunity from illegal poaching.…”
Section: Ujung Kulonmentioning
confidence: 99%
“…As such, the prevention of losses from hunting to supply the illegal pet trade remains the top conservation priority. With respect to deforestation, a scenario involving modest losses (1.2% annually) will not result in extinction, but lead to a reduced, remnant population (n = 135) within the 100-year time frame of the model (Smith et al 2017). Although the results from our 12.5 kilometres of reconnaissance walk "ground-truthing" exercise remain preliminary (Malone et al 2020), the observation of newly created irrigated rice paddies and ongoing small-scale deforestation within the park boundary are deeply concerning (Figure 4.8).…”
Section: Ujung Kulonmentioning
confidence: 99%
“…Halimun-Salak, and Mts. Dieng) found that inbreeding depression (3.14 lethal equivalents per diploid genome on juvenile mortality) had no measurable effect on extinction risk in the medium-long term (100 years) (Smith et al 2017). Supriatna et al (1999) and Andayani et al (2001, p. 774) noted that Breleasing confiscated gibbons … into the wild population on Java should be avoided except under the most stringent conditions of taxonomic identification.Ĥ owever, Javan gibbons have been released in at least five areas in recent years, viz.…”
Section: Implications For the Conservation Genetics Of Javan Gibbonsmentioning
confidence: 99%